Comparison of collum angle and labial crown-root angle of maxillary central incisor in Class I and Class II division 2 malocclusion - Pandey, Manju; Parajuli, Umesh; Dahal, Anita (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Variation in tooth morphology widely influences the achievement of optimum esthetics and stable occlusal relationship. This study was conducted to compare the collum angle and labial crown root angles in class I, class II division 2 malocclusions, using cephalometric radiographs, and to find a correlation between these angles. Methods: This cross-sectional study was conducted from March 2018 to January 2021 among patients visiting the department of Orthodontics at Gandaki Medical College. A total of 62 lateral cephalograms were included and equally divided into 2 groups: Angle’s Class I and Class II division 2. Cephalometric tracing was done to measure the collum angle and labial crown root of maxillary central incisors. Pearson’s correlation test and independent t-test were used. Results: There was a weak positive correlation (r=+0.348) between the angles in Class I group, (p=0.27) and a moderate positive correlation (r=+0.547) between the angles in Class II division 2 group (p<0.001). The mean collum angle was found to be greater in class II division 2 (11.90±6.86) than in class I (4.51±4.13) which was statistically significant (p<0.001). The mean labial crown root angle was found to be greater in class II division 2 (39.65±8.57) than in class I (30.23±5.20) which was statistically significant (p<0.001). Conclusions: There was no statistically significant correlation between collum angle and labial crown-root angle in class I groups. The mean of collum angle and labial crown-root angle was found to be greater in class II division 2 which were statistically significant in both angles.